How user knowledge of psychotropic drug withdrawal resulted in the development of person-specific tapering medication - Peter C. Groot; Jim van Os (SAGE Publishing, 2020)
Coming off psychotropic drugs can cause physical as well as mental withdrawal, resulting in failed withdrawal attempts and unnecessary long-term drug use. The first reports about withdrawal appeared in the 1950s, but although patients have been complaining about psychotropic withdrawal problems for decades, the first tentative acknowledgement by psychiatry only came in 1997 with the introduction of the 'antidepressant-discontinuation syndrome'. It was not until 2019 that the UK Royal College of Psychiatrists, for the first time, acknowledged that withdrawal can be severe and persistent. Given the lack of a systematic professional response, over the years, patients who were experiencing withdrawal started to work out practical ways to safely come off medications themselves. This resulted in an experience-based knowledge base about withdrawal which ultimately, in The Netherlands, gave rise to the development of person-specific tapering medication (so-called tapering strips). Tapering medication enables doctors, for the first time, to flexibly prescribe and adapt the medication required for responsible and person-specific tapering, based on shared decision making and in full agreement with recommendations in existing guidelines. Looking back, it is obvious that the simple practical solution of tapering strips could have been introduced much earlier, and that the traditional academic strategy of comparisons from randomised trials is not the logical first step to help individual patients. While randomised controlled trials (RCTs) are the gold standard for evaluating interventions, they are unable to accommodate the heterogeneity of individual responses. Thus, a more individualised approach, building on RCT knowledge, is required. We propose a roadmap for a more productive way forward, in which patients and academic psychiatry work together to improve the recognition and person-specific management of psychotropic drug withdrawal.